Upaya Pengembangan Candi Gedongsongo Sebagai Daya Tarik Wisata di Desa Candi Kecamatan Bandungan - Kris Cahyani Ermawati (Jurnal Pariwisata Indonesia, 2021)
Efforts to develop Gedongsongo Temple as a tourist attraction in Candi Village, Bandungan District. This was done to find out the efforts to develop the Gedongsongo temple as one of the featured tourist attractions in Candi Village, Bandungan District. The research method in this writing uses descriptive qualitative research, while to obtain the data of this study, the authors obtain data through observation, interviews, documentation and, literature study. By using 5 samples from the managers and tourists, as well as primary data sources obtained by the authors by conducting interviews aimed at obtaining the desired data and using SWOT analysis to describe the efforts to develop the Gedongsongo temple. In the development of the Gedongsongo Temple, several activities were carried out, including adding sports facilities, establishing a nature-based and rural culture-based tourism village, optimizing community involvement in supporting tourism activities, making tourism attraction packages that are contemporary and based on the uniqueness of local potential by the community, development tourism support facilities in Candi village, development of transportation facilities to facilitate tourist accessibility so that tourists get an unforgettable impression when visiting Gedongsongo temple. In addition, in the development process, Gedongsongo Temple also prioritizes environmental conservation, followed by cultural preservation and developing local potential. With the efforts that have been made, it is hoped that this Gedongsongo tourist attraction will be more attractive to tourists.